1999
DOI: 10.1063/1.873207
|View full text |Cite
|
Sign up to set email alerts
|

Wave and Joule heating in a rotating plasma

Abstract: Laboratory experiments were conducted to investigate ion energization by the wave and Joule heating mechanisms in plasma with a radial electric field and an axial magnetic field subjected to increasing ion–neutral collision frequency. Wave and Joule heating regimes were isolated and a transition between the two regimes was observed as the ion–neutral collision frequency was varied. The data show that the dissipation of energy occurs via the mechanism operating on the shortest time scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…In a recent paper we have treated the relationship and transition regimes between wave and collisional heating [Amatucci et al, 1999]. In particular, we have demonstrated in that work that for plasma conditions such that the ion-neutral collision frequency is sufficiently small to allow wave growth, energy dissipation which occurs through wave-particle interactions can be the primary channel of heating, even in those cases where both heating mechanisms are possible.…”
Section: Structured Electric Fields Broadband Waves and Transverse Ionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent paper we have treated the relationship and transition regimes between wave and collisional heating [Amatucci et al, 1999]. In particular, we have demonstrated in that work that for plasma conditions such that the ion-neutral collision frequency is sufficiently small to allow wave growth, energy dissipation which occurs through wave-particle interactions can be the primary channel of heating, even in those cases where both heating mechanisms are possible.…”
Section: Structured Electric Fields Broadband Waves and Transverse Ionmentioning
confidence: 99%
“…The previous experiments which focused on the relative dominance of wave or Joule heating [Amatucci et al, 1999] utilized electric fields which were directed radially inward. The reason for this is that in a cylindrical device, electric fields strong enough and localized enough to give rise to velocity shear driven ion cyclotron waves could be created without generating significant density gradients.…”
Section: Equilibrium Properties Of the Plasmamentioning
confidence: 99%
“…In Figure 4 temperature drops off sharply in both directions beyond the region where ν in /Ω i = 1, and it also reaches a maximum very near this point. As neutral pressure becomes low (λ in ≫ L E ) we expect there to be essentially no contribution to ion heating from collisions [ Amatucci et al , 1999].…”
Section: Summary Plot Of Ion Temperature Versus Pressurementioning
confidence: 99%
“…In this regard, for example, combined incoherent scatter radar in addition to satellite in situ measurements have unequivocally established that irregular field structures encountered in regions of small convective velocity are associated with ion heating. Earlier laboratory investigations [ Amatucci et al , 1999; Walker et al , 2001] have shown that there are two dominant processes responsible for ion temperature enhancement in the presence of transverse electric fields: (1) Joule, or collisional, heating in regions of high convective velocity and sufficient neutral density and, (2) wave heating via plasma instabilities in the presence of velocity shear. These works demonstrate conclusively the transition between these two forms of heating as a function of plasma neutral density.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of experiments simulating space plasma phenomena has been performed in the chamber [Walker et al, , 1997Amatucci et al, 1996Amatucci et al, , 1998Amatucci et al, , 1999. Table 1 outlines the basic plasma parameters for a 50 cm diameter argon plasma column as representative of various experimental environments in the SPSC.…”
Section: Chamber Environmentmentioning
confidence: 99%